An investigation into the response of the soil ecological environment to tourist disturbance in Baligou - Xiaolong Chen; Fangyuan Cui; Cora Un.In Wong; Hongfeng Zhang; Feiyang Wang (PeerJ, 2023)
The purpose of this study is to understand the response patterns of the soil ecological environment of the Macau Wetland Park to different levels of tourist interference and to provide a scientific basis for the rational development of the Bali Gou ecological tourism plan and the protection and management of the scenic area’s ecological environment. Combine the methods of field collection and laboratory physical and chemical data analysis to analyze the impact of the strength of tourism disturbance on the soil ecological environment of Baligou. During the tourist activities in Baligou, the human factors in the process have an impact on the physical aspects of the scenic area’s soil, such as soil bulk density, color tone, porosity, compactness, capacity, and leaf litter. In addition, pH value, soil enzyme activity, organic matter, and heavy metals in the soil have caused some interference. The overall data show that the dynamic of soil indicators is background area < buffer area < disturbed area,where the sample area is affected by human trampling and infrastructure construction and other disturbances leading to regular changes in the content of Pb and Cr in the sample soil, while the content of other heavy metals is lower than the national standard.The range of the most extreme values of the SRI integrated soil ecological response evaluation index was A1 disturbance area = 4.679 and C1 background area = 1.263, respectively. The larger the value of the SRI response index, the greater the impact and negative effect of the disturbance influence of tourism activities on the soil ecological environment of the scenic area, and the higher the level of response of the soil ecological environment of the scenic area to the disturbance of tourism activities. Moderate and reasonable tourism development activities play a role in promoting soil quality in scenic areas. Therefore, it is suggested to carry out reasonable ecological environment planning and take certain macro-measures to prevent the deterioration of the soil ecological environment, so as to achieve a win-win situation of ecological environmental protection while developing the tourism economy in scenic areas.